2014
DOI: 10.1007/s10228-014-0419-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of temperature on the growth and survivability of sichel larvae Pelecus cultratus reared under controlled conditions

Abstract: This study analyzed the influence of temperature on the rearing of sichel Pelecus cultratus larvae under controlled conditions. Five constant temperature regimes were tested: 14°C, 18°C, 22°C, 26°C and 30°C. The larvae were reared for 30 days in aquaria with 50 dm 3 working capacities. The larvae density was 40 individuals/ dm 3 and the fish larvae were fed live artemia nauplii. The assessment of the effect of thermal conditions during the rearing period on fish was based on the final size of fish, increment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 19 publications
2
15
0
Order By: Relevance
“…The incubation of sichel eggs took place in water of the optimal temperature (19.0 ± 0.1°C) (Kujawa, Furgała‐Selezniow, Mamcarz, Lach & Kucharczyk ), in five separate, close recirculation systems (Kujawa, Mamcarz, Kucharczyk & Skrzypczak ), containing water of the following salinity: 3, 6, 9, 12 and 15 ppt. Pro‐Reef marine salt by Tropic Martin was used to achieve the required salinity of water.…”
Section: Methodsmentioning
confidence: 99%
“…The incubation of sichel eggs took place in water of the optimal temperature (19.0 ± 0.1°C) (Kujawa, Furgała‐Selezniow, Mamcarz, Lach & Kucharczyk ), in five separate, close recirculation systems (Kujawa, Mamcarz, Kucharczyk & Skrzypczak ), containing water of the following salinity: 3, 6, 9, 12 and 15 ppt. Pro‐Reef marine salt by Tropic Martin was used to achieve the required salinity of water.…”
Section: Methodsmentioning
confidence: 99%
“…Throughout the whole rearing period, the daily light and darkness cycle was fixed, with 12 hours of day and 12 hours of night. The water temperature was 25.0±0.5ºC (± standard deviation) (Kujawa et al 2015), which was found as one from the thermal optimum range for sichel embryonic development. The concentration of water dissolved oxygen ranged from 7.1 to 7.7 mg O 2 dm -3 , while the value of pH was from 7.2 to 7.4.…”
Section: Methodsmentioning
confidence: 99%
“…The flow of water in a jar was regulated so that it mixed gently the whole contents of the jar. The spawn was incubated for 5 days in water of the temperature 18.5°C (Kujawa et al, 2015), which was found as an optimal temperature was sichel embryonic development. Larvae were allowed to hatch for one day since the first hatched individuals were spotted.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, increasing attention is now being paid to conservation of biological diversity through rebuilding populations of endangered species and their populations. These activities require effective protocols for artificial spawning and initial rearing of stocking material concerning different aspects of these biotechnological procedures (Kowalski et al, 2003;Augustyn, 2004;Kucharczyk et al, 2008;Targońska and Kucharczyk, 2011;Targońska et al, 2011a, Demény et al, 2012Żarski, 2012;Nowosad et al, 2014;Kujawa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%